Mirounga angustirostris Gill 1866 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Mirounga angustirostris Gill 1866 Mirounga angustirostris Gill 1866, Proc. Essex Inst. Salem, 5: 13. Type Locality: "California" restricted by Poole and Schantz (1942) to "St. Bartholomews Bay, lower California, Mexico." Clarified by Scheffer (1958) as "Bahía Tórtola (= Bahía San Bartolomé) 27°39'N, 114°51'W, Baja California, Mexico ". Vernacular Names: Northern Elephant Seal. Distribution: Mexico (Baja California), USA (SE Alaska to California). Conservation: IUCN – Lower Risk (lc). Discussion: Reviewed by Stewart and Huber (1993). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Carnivora, pp. 532-628 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 597, DOI: 10.5281/zenodo.7316519